Commentary on “Failer et al. (2022) Developmental endothelial locus-1 protects from hypertension-induced cardiovascular remodeling via immunomodulation” J Clin Invest 2022 (https://doi.org/10.1172/JCI126155) - Markus Sperandio (Pflügers Archiv - European Journal of Physiology, 2022)
Heart transplantation remains the gold standard therapy for patients with end-stage heart failure. However, post-transplant complications are considerable. Emerging evidence implicates the gut microbiome as a modifiable determinant of post-heart transplant outcomes through its influence on host immunity, metabolism, and inflammation. This Review synthesizes current understanding of gut microbiome dysregulation following solid organ transplantation, with particular emphasis on heart transplantation, examining mechanistic links underpinning important complications including allograft rejection, infection, metabolic dysfunction, and cardiac allograft vasculopathy. We critically evaluate bidirectional interactions between the gut microbiome and immunosuppressive drugs, assess the potential for microbiome profiling to serve as a predictive biomarker for post-transplant complications, and examine microbiome-targeted interventions including dietary modification, prebiotics, probiotics, and fecal microbiota transplant. Finally, we propose a translational roadmap to integrate microbiome science into heart transplant care to optimize immunosuppression, predict complications, and improve long-term outcomes for heart transplant recipients.